Advancing Performance Measurement for Public Health Emergency Preparedness: An Integrated Knowledge Translation Approach - Khan, Yasmin; O’Sullivan, Tracey; Brown, Adalsteinn; Gibson, Jennifer; Henry, Bonnie; Généreux, Mélissa; Schwartz, Brian (Prehospital and Disaster Medicine, 2019)
Introduction:Public health emergency management involves the timely translation of relevant evidence and effective coordination of diverse actors. In practice, this can be challenging in the absence of a common framework for action among diverse actors.Aim:To apply an Integrated Knowledge Translation (iKT) approach throughout the development of a conceptual framework and performance measurement indicators for public health emergency preparedness (PHEP), to ensure knowledge generated is relevant and useful to the field.Methods:The iKT approach was initiated by identifying a research question based on priorities from the field. The two phases of the study used participatory research methods as well as active engagement with potential end users at key study milestones. The Structured Interview Matrix (SIM) facilitation technique for focus groups and an expert panel using Delphi methodology were used to define the PHEP framework and performance measurement indicators, respectively. An advisory committee was assembled consisting of potential end-users of the research, in senior positions in applied and decision-making roles.Results:iKT was an essential component for this applied public health project, contributing to and enhancing the relevance of the knowledge generated. iKT contributed to the following: broad national engagement and interest in the study, successful recruitment in both phases, and engagement with decision-makers. This multi-dimensional participatory approach successfully generated knowledge that was important to the field demonstrated by relevance to practice and policy in jurisdictions across Canada. Furthermore, the approach fostered building resilience in local and national communities through collaboration.Discussion:The iKT approach was essential to generating knowledge that is relevant and useful to the field, mainly to promote health system preparedness and resilience. Future research to study the implementation of knowledge will be important to continue addressing the knowledge-to-action gap in health emergency management research.
Keywords: Généreux_Mélissa